Changes in coronary risk factors during comprehensive five-year community programme to control cardiovascular diseases (North Karelia project). Issue 6199 (10th November 1979) - Puska, P; Tuomilehto, J; Salonen, J; Neittaanmäki, L; Maki, J; Virtamo, J; Nissinen, A; Koskela, K; Takalo, T
Abstract : A comprehensive community programme to control cardiovascular diseases (CVD) in North Karelia, Finland, was carried out during 1972-7. The central intermediate objective of the programme was to reduce the prevalence of smoking, the serum cholesterol concentration, and raised blood-pressure values among the population of the area. The effect was evaluated by examining independent representative population samples in 1972 and 1977 in both the county of North Karelia and a matched control county. Over 10 000 subjects were studied each time, the participation rate being around 90%. The decrease that occurred in the risk factors, especially in men, was in general greater in North Karelia compared with the control county. When a multiple logistic function was used for the three risk factors an overall mean net reduction of 17% among men and 12% among women was observed in the estimated risk for coronary heart disease in North Karelia. This community programme effectively reduced the levels of the three main risk factors for CVD in the population, and thus mortality and morbidity from CVD should fall. This is assessed in further studies.